Granzyme K initiates IL-6 and IL-8 release from epithelial cells by activating protease-activated receptor 2. - Dion Kaiserman; Peishen Zhao; Caitlin Lorraine Rowe; Andrea Leong; Nicholas Barlow; Lars Thomas Joeckel; Corinne Hitchen; Sarah Elizabeth Stewart; Morley D Hollenberg; Nigel Bunnett; Andreas Suhrbier; Phillip Ian Bird (PLoS ONE, 2022)
Granzyme K (GzmK) is a tryptic member of the granzyme family of chymotrypsin-like serine proteases produced by cells of the immune system. Previous studies have indicated that GzmK activates protease-activated receptor 1 (PAR1) enhancing activation of monocytes and wound healing in endothelial cells. Here, we show using peptides and full length proteins that GzmK and, to a lesser extent the related protease GzmA, are capable of activating PAR1 and PAR2. These cleavage events occur at the canonical arginine P1 residue and involve exosite interactions between protease and receptor. Despite cleaving PAR2 at the same point as trypsin, GzmK does not induce a classical Ca2+ flux but instead activates a distinct signalling cascade, involving recruitment of β-arrestin and phosphorylation of ERK. In epithelial A549 cells, PAR2 activation by GzmK results in the release of inflammatory cytokines IL-6 and IL-8. These data suggest that during an immune response GzmK acts as a pro-inflammatory regulator, rather than as a cytotoxin.